46th AIAA Fluid Dynamics Conference 2016
DOI: 10.2514/6.2016-3640
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Order Modeling of Turbulent Flows Using Statistical Coarse-graining

Abstract: Traditional sub-grid models for Large Eddy Simulations (LES) of turbulence rely on theoretical and physical arguments and are known to be inadequate in many applications. This work investigates the use of the Mori-Zwanzig formalism, a concept that originates from non-equilibrium statistical mechanics, to develop sub-grid models for LES. The mechanics of the generalized Langevin equation (GLE) are considered and a methodology for directly solving the orthogonal dynamics equation is presented. This process is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Most notably, Stinis and co-workers [44,45,46,47,48,49] have developed several models for approximating the memory, including finite memory and renormalized models, and examined their application to the semi-discrete systems emerging from Fourier-Galerkin and Polynomial Chaos Expansions of Burgers' equation and the Euler equations. Application of MZ-based techniques to the classic POD-ROM approach has not been undertaken.This manuscript leverages work that the authors have performed on the use of the MZ formalism to develop closure models of partial differential equations [50,51,52,53,54]. In addition to focusing on the development and analysis of MZ models, the authors have examined the formulation of the MZ formalism within the context of the VMS method [54].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most notably, Stinis and co-workers [44,45,46,47,48,49] have developed several models for approximating the memory, including finite memory and renormalized models, and examined their application to the semi-discrete systems emerging from Fourier-Galerkin and Polynomial Chaos Expansions of Burgers' equation and the Euler equations. Application of MZ-based techniques to the classic POD-ROM approach has not been undertaken.This manuscript leverages work that the authors have performed on the use of the MZ formalism to develop closure models of partial differential equations [50,51,52,53,54]. In addition to focusing on the development and analysis of MZ models, the authors have examined the formulation of the MZ formalism within the context of the VMS method [54].…”
mentioning
confidence: 99%
“…This manuscript leverages work that the authors have performed on the use of the MZ formalism to develop closure models of partial differential equations [50,51,52,53,54]. In addition to focusing on the development and analysis of MZ models, the authors have examined the formulation of the MZ formalism within the context of the VMS method [54].…”
mentioning
confidence: 99%
“…The initial conditions are generated following a specific energy spectrum [23,34] shown in eq. (32).…”
Section: Training With Multiple Trajectories With Random Initializationmentioning
confidence: 99%
“…It can be shown that, when the original dynamical system is linear, that solutions to the orthogonal dynamics equation can be obtained by solving a corresponding set of auxiliary ordinary differential equations. This methodology was suggested in [22] as a procedure to approximate the orthogonal dynamics in non-linear systems and was further developed and investigated in detail in [23]. To gain insight into the orthogonal dynamics, we consider a simple linear system.…”
Section: A the Orthogonal Dynamics Equation And The Memory Kernelmentioning
confidence: 99%